Sosialisasi Pemilahan Sampah dan Pelatihan Pembuatan Kompos di Desa Luwijawa, Kecamatan Jatinegara, Kabupaten Tegal - Rifqie Mardiansyah Purmadi; Rahmi Jamza; Sugeng Santoso; Fitrianingrum Kurniawati; Budi Nugroho; Candra Budiman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Luwijawa Village is a village located in Jatinegara District, Tegal Regency, Central Java Province. The village which has an area of 257,285 ha, the majority of its residents work as farmers. Agriculture carried out is rice farming with rice and corn as the main crops, as well as plantation crops such as coffee and durian. Villagers still use chemical fertilizer as a nutrient provider for plants, as well as the problem of rubbish that is still burned or thrown away by residents. The activity of sorting waste and training on composting was carried out to educate the public, especially PKK women, on how to manage waste to compost fertilizer. The socialization is done by the lecture method. The speaker explained the material using a power point and continued with video playback. Participants can ask questions after the socialization activities have been completed. Socialization activities and compost making training were carried out on different days. Compost making training is conducted with residents from organic waste. Organic waste obtained from residents' kitchen waste is cut to pieces and mixed with bioactivators (EM- 4). The ingredients that have been mixed are then put into a bucket and tightly closed so that no air enters, this is done to maximize the work of the bioactivator in the fermentation process. Compost making training activities took place well, there were quite a lot of participants, with relatively high enthusiasm. This is evidenced by the many questions asked by participants in the series of activities. Participants have been able to distinguish organic and inorganic waste, and have the desire to make their own compost with materials available in the surrounding environment. Keywords: compost, garbage, socialization